Kedudukan Menteri Triumvirat Dalam Ketatanegaraan Indonesia - Gunawan, Edwin; Abas, Muhamad; Akbar, Muhammad Gary Gagarin (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
The Triumvirate Ministers are the three ministers namely the Minister of Foreign Affairs, Minister of Home Affairs, and Minister of Defense who are said to be carrying out presidential duties if the President and Vice President resign in the middle of their term of office simultaneously. This is stated in the mandate of the 1945 Constitution of the Republic of Indonesia as the basis for implementing statutory regulations. This writing aims to explore the issues raised in this study, namely, the position of the Minister of the Triumvirate in the Indonesian constitution and legal settlement in the event of a dispute in the formation of the three Ministers of the Triumvirate. In this study the authors used the normative juridical method. The results of this study are that the position of the minister of the Triumvirate is confirmed in the 1945 Constitution of the Republic of Indonesia Article 8 paragraph (3), but it is not clarified by other laws and regulations, so that his position is not standardized by law. And also if there is a dispute within the Triumvirate Ministers, the resolution is that the Constitutional Court has the duty and authority to resolve disputes between the Triumvirate ministers regarding who has the most authority to fill presidential duties.